Microbial communities in the rhizosphere and the root of lettuce as affected by Salmonella-contaminated irrigation water. Issue 9 (13th July 2018) - Zhang, Yuping; Jewett, Christian; Gilley, John; Bartelt-Hunt, Shannon L; Snow, Daniel D; Hodges, Laurie; Li, Xu
ABSTRACT: Reclaimed wastewater is increasingly used as a source of irrigation water in croplands. The enteric pathogens in reclaimed wastewater may accumulate in soil and plants and cause food safety concerns. The objective of this study was to determine the effects of irrigation water containing Salmonella on the microbial communities in the rhizosphere and in the root of lettuce. The effects were also examined with three variables (soil texture, lettuce cultivar and harvest time) in a factorial design. Analyses of the 16S rRNA gene sequences show that the microbial communities in the root were significantly different from those in the rhizosphere, although ∼80% of the microbes in the root originated from the rhizosphere. Salmonella in irrigation water significantly altered the structure of the microbial community in the rhizosphere, but not in the root. Salmonella internalized in lettuce root was observed when contaminated water was used for irrigation. Compared to lettuce cultivar and harvest time, soil texture played a more significant role in shaping the bacterial communities in the rhizosphere and in the root. Results from this study could advance understanding about the long-term impact of reclaimed wastewater as a source of irrigation water on the microbiota associated with leafy green vegetables. Abstract : When used for irrigation on lettuce, reclaimed wastewater containing Salmonella could significantly alter the microbiome in the rhizosphere, but not that in the root.